Effects of droplet size and spray interval on root-to-shoot ratio, photosynthesis efficiency, and nutritional quality of aeroponically grown butterhead lettuce - Tunio, Mazhar Hussain; Gao, Jianmin; Qureshi, Waqar Ahmed; Sheikh, Sher Ali; Chen, Jiedong; Chandio, Farman Ali; Lakhiar, Imran Ali; Solangi, Kashif Ali (International Journal of Agricultural and Biological Engineering, 2022)
The proper selection of the atomizer (droplet size) and nutrient solution spray interval is one of the most important factors to be investigated in aeroponics systems for sustainable agriculture. The aim of this study was to research the effects of four aeroponics atomizing nozzles (one air-assisted; A1, two air-less; A2 and A3, and one ultrasonic fogger; A4) with droplet sizes of 11.24 µm, 26.35 µm, 17.38 µm, and 4.89 µm, respectively, four spray intervals (15 min (I1), 30 min (I2), 45 min (I3) and 60 min (I4)) at a 5 min of constant spray time by atomizing the Hoagland’s nutrient solution on growth, root-to-shoot ratio, photosynthesis characteristics, pigments, and nutritional quality of the aeroponically grown lettuce. The experimental results demonstrated that in A1 atomizer and I2 interval, the growth, photosynthesis efficiency, chlorophyll, carotenoids, and nutritional values of the lettuce were significantly higher compared to that grown in A2 and A3 atomizers at all spray intervals. The shoot developments were more constrained than root, prominent to the alteration of root-to-shoot ratio (fresh and dry) in the influence of different droplet sizes and spray intervals. Moreover, the plants did not grow well in A4 atomizer associated with proposed spray intervals. The results disclosed that there was an obvious interaction between droplet sizes (atomizers) and spray intervals for growth, the ratio of root to shoot, photosynthesis efficiency, pigments, and nutritional quality of the aeroponically grown lettuce. This research study increases the awareness of the proper droplet size (atomizer) and the regulation of nutrient solution spray interval for leafy vegetables grown in an aeroponics system. Keywords: aeroponics system, atomizers, droplet sizes, photosynthesis efficiency, chlorophyll contents, quality of lettuce DOI: 10.25165/j.ijabe.20221501.6725 Citation: Tunio M H, Gao J M, Qureshi W A, Sheikh S A, Chen J D, Chandio F A, et al. Effects of droplet size and spray interval on root-to-shoot ratio, photosynthesis efficiency, and nutritional quality of aeroponically grown butterhead lettuce. Int J Agric & Biol Eng, 2022; 15(1): 79–88.